Estudio morfológico del cysticercus tenuicollis en ovinos faenados en mataderos. - Aguilera Vizuete, Mauricio Rafael (2021)
The production of sheep in Ecuador it is carried out by small producers or the peasantry in general, with poor sanitary management. In the present research a study is carried out through an inspection post mortem about the morphological, molecular, prevalence and distribution characteristics of the Cysticercus tenuicollis in slaughtered sheep in slaughterhouses. Samples were taken from 200 slaughtered sheep since January to December 2020, resulting 82 positive cases to the parasite (28 females and 54 males); your bodily condition is of 2 to 3 over 5 and their ages from 11 months to 3 years; the affected organs and number of cysts found were omentum with 191, liver with 92, lung with 47, female reproductive system 5 and hearth 1. The cyst size varies from 2 cm to 15cm; the weight of 2gr to 16gr and the observed characteristics in the laboratory are serous membrane, transparent, blood supply, transparent liquid with protein content, a single scholex, four suction cups, double hook crown, in the liver and lungs they form hemorrhagic migration paths. In the molecular study of the Cysticercus tenuicollis integrity was maintained of the samples, guaranteeing extraction, assessment and quantification of the DNA, which satisfactorily reflects the sequence of 20 analyzed samples which represent 100%. As a result the correlation is reflected of the amplification of the primers NAD_COX1 that were specific and its identification was optimal. The used primers were specific for cysticerci, in this case 5´CARTTTCGTAAGGGBCCWAAWAAGGT direct and 5´- CCAATTTCYTGAAGTTAACAGCATCA reverse keeping the behavior for cestodos.